An Own and Assimilated Layer in our Linguistics - Raimjanova Makhbuba Nomanovna (Genius Journals, 2022)
This article provides a brief overview of the words of Islam that have entered Uzbek linguistics and the reasons for their penetration
Keywords: Neologisms; Persian-Tajik language; English; the popularization of new words